Rebranding design - Debit, Johan, ....- (Mulgrave, Victoria : The Images Publishing Group Pty Ltd, 2017)
Explores how to design for rebranding concepts that result in optimum commercial success Rebranding is a delicate exercise that can often have many pitfalls, both for the brand that ventures into such a project and for the agency who has been chosen to engage with this process. The business undergoing rebranding must ask the following questions: is this an appropriate time for such substantive work? Are we talking about a soft evolution or metamorphosis? Does this rebranding address a clearly identified problem, and can it represent a genuine asset for development? For designers, even if these questions remain central, other issues also arise: how to produce a distinctive project in the face of a profusion of branding works available online? How to produce relevant and appreciated work in a challenging economic and social environment? This book brings together some of the best rebranding projects in the world and addresses these key issues formally and with real substance. It places the crucial (and sometimes underestimated) role of the brand design into the developmental processes of companies, institutions or associations.
Keywords: Merken; Rebranding